2016
DOI: 10.1016/j.ejmech.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Non-symmetrical furan-amidines as novel leads for the treatment of cancer and malaria

Abstract: NRH:quinone oxidoreductase 2 enzyme (NQO2) is a potential therapeutic target in cancer and neurodegenerative diseases, with roles in either chemoprevention or chemotherapy. Here we report the design, synthesis and evaluation of non-symmetrical furan-amidines and their analogues as novel selective NQO2 inhibitors with reduced adverse off-target effects, such as binding to DNA. A pathway for the synthesis of the non-symmetrical furan-amidines was established from the corresponding 1,4-diketones. The synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In addition, we tested the compounds against a small panel of human cancer cell lines. In recent years, numerous reports have shown that compounds with antimalarial activity may represent potential anticancer agents, and vice versa [4749]. The results obtained were compared to our previous findings on asexual P. falciparum and HEK293 cells [22] .…”
Section: Discussionmentioning
confidence: 83%
“…In addition, we tested the compounds against a small panel of human cancer cell lines. In recent years, numerous reports have shown that compounds with antimalarial activity may represent potential anticancer agents, and vice versa [4749]. The results obtained were compared to our previous findings on asexual P. falciparum and HEK293 cells [22] .…”
Section: Discussionmentioning
confidence: 83%
“…NQO2 is a potential target for cancer chemotherapy as its inhibition has therapeutic and/or preventative potential. In our laboratory, non-symmetrical furanamidine 1 (Figure 1) and para-substituted analogues were identified as novel lead inhibitors of NQO2 with both anti-cancer and anti-malarial activities [3]. Here, further modifications to these non-symmetrical furan-amidines have been evaluated.…”
Section: Evaluation Of Analogues Of Furan-amidines As Inhibitors Of Nqo2mentioning
confidence: 99%
“…Here, further modifications to these non-symmetrical furan-amidines have been evaluated. Some of the non-symmetrical furan-amidines [3] showed poor water solubility, therefore the furan ring of 1 was replaced by more water-soluble isosteric heterocycles, including imidazole and oxazole. The lead NQO2 furan inhibitor possesses the highly basic amidine group, which will potentially decrease its passive diffusion and oral bioavailability [4,5].…”
Section: Evaluation Of Analogues Of Furan-amidines As Inhibitors Of Nqo2mentioning
confidence: 99%
See 1 more Smart Citation
“…Pt 3 L 3+ shows the strongest effects, with a destabilisation of the polynucleotide double helix that brings about a T m decrease of about 4° C. <Figure 5near here> Melting temperature changes are not a direct measure of affinity but their extent allows to comment on the ability of the binding molecule to alter the stability of the double strand. In the case of intercalation of a small planar molecule between the base pairs a major stabilisation effect is observed (usually ∆Tm>10° C,[18]),…”
mentioning
confidence: 99%